INTERNALISASI KONSEP WARISAN DALAM SURAT AN-NISĀ’ AYAT 7–11 PERSPEKTIF TAFSIR AL-ṬHABARI DALAM PEMBELAJARAN PENDIDIKAN ISLAM DI PADANG PARIAMAN - M. Sanusi Ibrahim; Nasruddin; Muhammad Syahrial Razali Ibrahim (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Islamic education has a strategic role in internalizing the values ​​of justice, humanity, and social responsibility derived from the Qur'an, particularly through the learning of inheritance law (mawaris) based on Surah An-Nisa' verses 7-11. This study aims to analyze the concept of inheritance from the perspective of Tafsir Al-Ṭhabari and its relevance in Islamic Education learning in Padang Pariaman. This study uses a qualitative method with a thematic-analytical interpretation approach combined with the tahlili and muqārin methods, with primary data sources in the form of the book Jāmi‘ al-Bayān fī Ta’wīl al-Qur’ān by Al-Ṭhabari and secondary data from authentic hadiths and Islamic interpretation and education literature. The results of the study indicate that Al-Ṭhabari interprets inheritance verses not merely as technical rules for the distribution of property, but as instruments of sharia to uphold distributive justice, protect vulnerable groups such as orphans and the poor, and instill moral responsibility in Muslim families. The research findings confirm that inheritance distribution, including the 2:1 ratio between men and women, is understood as contextual proportional justice, not gender discrimination. The implications of this study indicate that Islamic education learning needs to integrate normative, historical, and ethical aspects so that students not only understand inheritance law from a fiqh perspective but are also able to internalize the values ​​of social justice, caring, and trustworthiness in community life.